2022
DOI: 10.4038/sljpsyc.v13i1.8358
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of COVID-19 among a cohort of Sri Lankan medical students: Preliminary results

Abstract: Previous studies report that the COVID-19 pandemic has a negative effect on the psychological wellbeing of medical students. We aimed to determine the psychological impact of COVID-19 and its associated factors among a cohort of Sri Lankan medical students, using online versions of a demographic questionnaire and the validated Sinhala and Tamil versions of the DASS-21. Of the 418 students, majority were females, aged between 20-25 years. In the study group, 40 (9.6%), 105 (25.1%) and 7 (1.6%) of participants s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
1
1
1
Order By: Relevance
“…This study found no significant differences between economic affluence, stress and depression. Our study findings contradict previous studies (Abayabandara-Herath, et al, 2022;Mehareen, et al, 2021;Rehman, et al, 2021;Shafiq, et al, 2021) reported that students with poor economic conditions were more prone to having higher levels of depression and stress. This could be because private university students are likely to have better socioeconomic status.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This study found no significant differences between economic affluence, stress and depression. Our study findings contradict previous studies (Abayabandara-Herath, et al, 2022;Mehareen, et al, 2021;Rehman, et al, 2021;Shafiq, et al, 2021) reported that students with poor economic conditions were more prone to having higher levels of depression and stress. This could be because private university students are likely to have better socioeconomic status.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, the prevalence of SAD is significantly higher among the female students as compared with the male students. This finding is consistent with previous studies (Abayabandara -Herath, et al, 2022;Huang, et al, 2021;M. S. Islam, et al, 2020;Verma, et al, 2021).…”
Section: Discussionsupporting
confidence: 94%
“…The likelihood of depression was positively correlated with the frequency of exposure to threatening life events among these students [ 27 ]. Depression was also associated with economic difficulties among university students [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is necessary to effectively report the psychological disturbances of Sri Lankan undergraduates due to Covid-19-how it could affect their academic performances; how this type of unexpected circumstances affect the very gentle personalities the young population have; and how their normal education which is not normal to them as previous is impacted. However, studies related to other undergraduates are scarce 40,[58][59][60] compared to the studies done among medical undergraduates in Sri Lanka 12,[61][62][63][64] . Several research findings about the prevalence of psychological issues and factors associated with the Covid-19 disease among undergraduates in Sri Lanka were reported 7,40,58,59,62,63 12 , that there were significant psychosocial stressors, and it may tend to develop more psychological morbidity among that population.…”
Section: Prevalence Of Stress Anxiety and Depressive Symptomsmentioning
confidence: 99%
“…In some literature, lower levels of stress and anxiety were found. Covid-19 epidemic had a significant impact on medical students' psychological health (25.1%) and (1.6%) of students reported having anxiety and stress levels that were over the recommended levels 61 . One study done in Sri Lanka in 2020, including Indian and Russian undergraduates, reported that 3.16% of undergraduates experienced stress and 11.58% of undergraduates had anxiety due to Covid-19 which was remarkably lower than the current study 7 .…”
Section: Prevalence Of Stress Anxiety and Depressive Symptomsmentioning
confidence: 99%